All‐Solution‐Processed Transparent Thin Film Transistor and Its Application to Liquid Crystals Driving. (22nd April 2013) - Lee, Kwang‐Ho; Kim, Sang‐Mook; Jeong, Huisu; Pak, Yusin; Song, Hui; Park, Jeongpil; Lim, Keon‐Hee; Kim, Jae‐Hoon; Kim, Youn Sang; Ko, Heung Cho; Kwon, Il Keun; Jung, Gun‐Young
<x xml:space="preserve">Abstract</x> All‐solution‐processed transparent thin film transistors (TTFTs) are demonstrated with silver grid source/drain electrodes, which are fabricated by printing and subsequent silver nanoparticles solution coating, which allows continuous processing without using high vacuum systems. The silver grid electrode shows a reasonable transmittance in visible range, moderate electrical conductance and mechanical strength. The TTFTs are employed to drive liquid crystal cells and demonstrate a successful switching operation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>